ANALISA SUPPLY CHAIN MANAGEMENT TERHADAP BUSINESS PERFORMANCE PADA PERUSAHAAN INDUSTRI MANUFAKTUR TEKSTIL DAN PRODUK TEKSTIL DI JAWA TENGAH - Amanda Grace Andani; Fuad Mas'ud (Jurnal Akuntansi dan Pajak, 2023)
This study seeks to analyze supply chain management on business performance in manufacturing industry companies. The large number of manufacturing companies that are in the development stage increases the importance of understanding and managing supply chain management well to continue to be able to support the competitive advantage of companies in the future. This research was driven by inconsistent research results which provide the potential to conduct further research on supply chain management. This research uses quantitative methods. The type of data used in this research is primary and secondary data. The research conducted took a population of 808 Textile and Textile Product Manufacturing Companies in Central Java (Ministry of Industry, 2022). The research will use the Cluster Sampling technique with a sample of 25 companies. This study uses the Structural Equation Model (SEM) method with the help of the AMOS application. There are 2 models of techniques used in this study, namely Confirmatory Factor Analysis and Regression Weight. The results of this study prove that partnership has a positive effect on business performance, information sharing has a positive effect on business performance, supply chain management mediates the positive effect of partnership on business performance, supply chain management mediates the positive effect of information sharing on business performance. and supply chain management has a positive effect on business performance. Keywords: supply flow; business performance; partnerships; information sharing